The α‐Thioglycoligase Derived from a GH89 α‐N‐Acetylglucosaminidase Synthesises α‐N‐Acetylglucosamine‐Based Glycosides of Biomedical Interest. Issue 4 (26th January 2017) - Tshililo, Ndivhuwo Olga; Strazzulli, Andrea; Cobucci‐Ponzano, Beatrice; Maurelli, Luisa; Iacono, Roberta; Bedini, Emiliano; Corsaro, Maria Michela; Strauss, Erick; Moracci, Marco
Abstract: We report here on the preparation of a novel α‐thioglycoligase that can be used for the fast and efficient synthesis of α‐ N ‐acetylglucosamine‐based glycosides. Using the α‐ N ‐acetyl‐glucosaminidase from Clostridium perfringens of family GH89 (according to the Carbohydrate Active Enzymes classification) as starting point, we prepared mutants in the acid/base residue glutamic acid 483 that were found to have different synthetic efficiencies (maximal yields >80% after 24 h) in the presence of an activated donor and suitable acceptors. The synthetic potential of the Glu483 alanine mutant as an α‐thioglycoligase – only the third biocatalyst with this stereospecificity reported to date, and the first selective for the N ‐acetylglucosamine moiety – was demonstrated by producing for the first time N ‐acetyl‐α‐d ‐glucosaminyl azide and N ‐acetylglucosamine α‐thioglycosides in high yields. To showcase the application of such compounds, we show that they offer the wild‐type CpGH89 protection from thermal unfolding, demonstrating their potential as pharmacological chaperones for the treatment of mucopolysaccharidosis IIIB (Sanfilippo syndrome). Abstract :